2020
DOI: 10.3390/ani10010112
|View full text |Cite
|
Sign up to set email alerts
|

Citrus Extract Improves the Absorption and Utilization of Nitrogen and Gut Health of Piglets

Abstract: The purpose of this study was to investigate the effects of citrus extract (CE) on plasma free amino acids, intestinal morphology and enzymes activity, fecal nitrogen and phosphorus emissions in piglets. The experiment was performed on 144 weaned piglets (Duroc × Landrace × Large White) divided into three groups. Control (CON), fed a basic diet; Antibiotic (ANTI), fed a basic diet supplemented with 75 g/t chlortetracycline; Citrus extract (CE), fed a basic diet supplemented with 300 mL/t CE. The albumin conten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 44 publications
(59 reference statements)
2
8
0
Order By: Relevance
“…Therefore, it is reasonable to suggest that the CE‐induced increase of plasma glucose may partly explain the increase of the growth performance by CE treatment. In addition, dietary CE supplementation also affected urea metabolism in broilers, as indicated by the decreased plasma urea concentration, which is consistent with a previous study, which also found CE decreased urea concentration in weanling piglets fed a CE‐supplemented diet 20 . Blood urea is the main end‐product of AA catabolism in the host, and urea concentration is recognized as an indicator of the protein requirement and AA utilization 43 .…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…Therefore, it is reasonable to suggest that the CE‐induced increase of plasma glucose may partly explain the increase of the growth performance by CE treatment. In addition, dietary CE supplementation also affected urea metabolism in broilers, as indicated by the decreased plasma urea concentration, which is consistent with a previous study, which also found CE decreased urea concentration in weanling piglets fed a CE‐supplemented diet 20 . Blood urea is the main end‐product of AA catabolism in the host, and urea concentration is recognized as an indicator of the protein requirement and AA utilization 43 .…”
Section: Discussionsupporting
confidence: 90%
“…The current study found that dietary supplementation with CE significantly increased plasma total protein, albumin and glucose concentrations. Previous studies reported similar findings indicating that dietary supplementation with CE increased serum total protein concentration in broilers 4 and plasma albumin concentration in weanling piglets 20 . Liver is the main source of blood proteins, and dietary AAs are the preferred precursor for hepatic protein synthesis in animals 40 .…”
Section: Discussionsupporting
confidence: 52%
See 3 more Smart Citations